Security issues in 5G device to device communication - Khan, A.S.; Yasir, Javed; Johari, Abdullah; Nazim, J.M.; Khan, N. (IJCSNS, 2017)
5G is a promising technology that will support high connectivity and device to device communication. It also promises to improve the existing technologies and will support them. Existing LTE-A utilize centralized communication scheme where all the authentication mechanisms need to go through the base station. This centralized authentication mechanism may generate authentication and key management overhead as well as computational complexity, thus not in line with the 5G requirements. On the other hand, distributed communication scheme lacks hop by hop authentication, thus, it is challenging to share the initial security credentials within the relay stations at multi-hop. Secondly, distributed communication scheme required decode and forward relays, a partial intelligent relays that can act as a semi base stations. Such relays are known as non-transparent relays. However, inclusion of such intelligent relays can leads towards a ROGUE RELAY STATION (RRS) attacks, which consequently generate Replay attacks, DoS and the MITM (where mutual authentication is absent). RRS can generate interleaving attack even in the presence of mutual authentication.